ChemInform Abstract: Heterogeneous Phase Microwave‐Assisted Reactions under CO2 or CO Pressure. Issue 43 (7th October 2016) - Gaudino, Emanuela Calcio; Rinaldi, Laura; Rotolo, Laura; Carnaroglio, Diego; Pirola, Camillo; Cravotto, Giancarlo
Abstract: Review: 87 refs.